GREEN TAXONOMY: ESSENCE, APPLICATION AND EFFECTIVENESS (British Journal of Global Ecology and Sustainable Development, 2024)
The article presents the essence of the “green taxonomy”, the relevance and importance of its application in ensuring sustainable development, the need to produce a “green taxonomy” in Uzbekistan and the effectiveness of its implementation.